Nanomaterials: Removal processes and beneficial applications in treatment. Issue 12 (1st December 2013) - Boyd, Glen R.; Tuccillo, Mary Ellen; Sandvig, Anne; Pelaez, Miguel; Han, Changseok; Dionysiou, Dionysios D.
Abstract : Nanomaterials are typically defined as particles with at least one dimension measuring < 100 nm. Limited information is currently available and more research is needed regarding the occurrence of these materials in source water and the effectiveness of water treatment processes at removing engineered nanomaterials. Engineered nanomaterials also offer opportunities for improving the operation and performance of drinking water treatment systems. Nanomaterials are currently being developed for the removal of trace organics and metals and for disinfection through application to membranes (nanomaterial‐enhanced or nanoreactive membranes), ion exchange, and sorption processes. Nanomaterials can remove contaminants of emerging concern by oxidation processes (e.g., titanium dioxide photocatalysis) and abiotic reduction (e.g., nanozerovalent iron). They are also being used in nanosensors for water quality monitoring. Ongoing development of nanomaterials is expected to continue contributing improvements to treatment systems with the potential for increasing the availability of safe drinking water supplies.